The Effect of Good Governance, Government Spending on Health and Education on HDI in E7 Countries - Ajeng Putri Mellinia (Efficient: Indonesian Journal of Development Economics, 2024)
This study aims to determine the effect of government spending on health and education sectors on HDI in Emerging Seven Countries (E7) through good governance as an intervening variable. The data used in this study are panel data with time series data from 2006 to 2020 and cross section data for 7 countries in E7. Using HDI data as the dependent variable, government expenditure data in the health and education sectors as independent variables, and good governance data which includes control of corruption and government effectiveness as intervening variables. The sobel test is used to determine the effect of the independent variable on the dependent variable through the intervening variable. Based on the results of panel data regression, it is known that good governance variables, government spending in the education and health sectors directly have a significant effect on HDI. Government spending variables in the health and education sectors on HDI through control of corruption also have a significant effect. While the variable of government expenditure in the health and education sectors through government effectiveness has no significant effect on HDI in E7 countries.